2017
DOI: 10.1038/srep45567
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a smartphone-based EEG among people with epilepsy: A prospective study

Abstract: Our objective was to assess the ability of a smartphone-based electroencephalography (EEG) application, the Smartphone Brain Scanner-2 (SBS2), to detect epileptiform abnormalities compared to standard clinical EEG. The SBS2 system consists of an Android tablet wirelessly connected to a 14-electrode EasyCap headset (cost ~ 300 USD). SBS2 and standard EEG were performed in people with suspected epilepsy in Bhutan (2014–2015), and recordings were interpreted by neurologists. Among 205 participants (54% female, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 16 publications
3
46
0
Order By: Relevance
“…when comparing wet and dry electrodes). This result agrees with our previous study, where trained neurologists were clinically investigating the data (12), and with a number of other studies done on Epoc Emotiv in different contexts (11,20). However, to our best knowledge, a fully automated approach in combination with the resting state data was not previously reported.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…when comparing wet and dry electrodes). This result agrees with our previous study, where trained neurologists were clinically investigating the data (12), and with a number of other studies done on Epoc Emotiv in different contexts (11,20). However, to our best knowledge, a fully automated approach in combination with the resting state data was not previously reported.…”
Section: Resultssupporting
confidence: 92%
“…Unfortunately, all described methods require performing the data collection under carefully controlled conditions, which is not always possible in a clinical environment. Some earlier publications (12,20) proposed a solution based on professional human assessment, however this approach brings a number of problems, such as subjective judgement and high variation of the scores (12). Therefore, an objective, computer-based way of comparison is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Cooperation with local partners is essential for its success. A recent study has shown the potential impact of teleneurology for diagnosing epilepsy, using wireless consumer-grade EEG recordings [21]. We believe that our experience could be another step forward in this innovative field and may stimulate other contributions that may help to close the epilepsy diagnostic gap in regions where the burden of this disabling disease is highest.…”
Section: Discussionmentioning
confidence: 75%
“…Over the past few years, research showed that the signals acquired via wireless mobile EEG headset devices are similar to those obtained with standard EEG laboratory equipment and traditional rating scales or diagnostic assessments [112,113]. Due to the increasing interest in mobile EEG applications, our search revealed several EEG apps, but not many were designed for research or medical applications.…”
Section: Eeg Systems and Smartphonesmentioning
confidence: 99%